What's in a Word? Falsified/Counterfeit/Fake Medicines - The Definitions Debate. Issue 1 (2017) - Isles, Mike
There is a rising tide of criminal activity to manufacture and distribute falsified, counterfeit, or fake medicines. The exact size of this problem is unknown but estimates vary from US$75 billion to US$200 billion per year, and evidence clearly demonstrates it is on the increase. Depending on the world region, infiltration into the legitimate supply chain versus the illegitimate (e.g., the internet) varies greatly. However, what is certain is that the direction of travel by regulatory agents is to develop supply chains that allow access to medicines via the World Wide Web. Within this context, there has been a long-running debate about how to correctly describe the various forms of medicines that are fraudulently or otherwise manufactured and distributed. This article attempts to describe the evolution of the definitions and recommends that a consensus be formed to describe such medicines that reach the public: Falsified medicine: This being the term used and defined in the Falsified Medicines Directive and which is primarily concerned with public health. Counterfeit medicine: This is closely associated and legally defined within intellectual property legislation and concentrates on trademark protection. Fake medicine: This is the term that best serves to communicate with the public to raise awareness about the phenomenon.